Effects of Dietary Rhodobacter sphaeroides Protein Substitution of Fishmeal and Coenzyme Q10 Supplementation on Growth Performance, Intestinal Microbiota and Stress Tolerance of Litopenaeus vannamei in Acute Low Salinity - Liao, Zhihong; Gong, Yangyang; Wang, Ziqiao; Wang, Yingjie; Yao, Rong; Chen, Mengdie; Wei, Dan; Zhao, Wei; He, Xuanshu; Niu, Jin (Frontiers in Marine Science, 2022)
A 56-day culture experiment followed by an acute low salinity challenge was conducted to evaluate the effects of Rhodobacter sphaeroides protein (RSP) substitution of fishmeal and Coenzyme Q10 (CoQ10) supplementation on growth performance, intestinal microbiota and compressive capacity of Litopenaeus vannamei (L. vannamei). Four experimental diets were formulated: FM diet (20% fishmeal), RSP diet (20% RSP instead of 20% fishmeal), CoQ10 diet (20% fishmeal supplemented with CoQ10 at 0.08 g kg–1), RSP + CoQ10 diet (20% RSP supplemented with CoQ10 at 0.08 g kg–1). The obtained results were denoted that L. vannamei fed CoQ10 diet could improve growth performance (weigh gain and specific growth rate), condition factor and crude lipid, and decrease hepatosomatic index, but no differences were found in survival rates. High throughput sequencing on intestinal microbiota indicated that intestinal microbiota of L. vannamei consisted mainly of Proteobacteria and Firmicutes. The species richness of the RSP diet was remarkably higher than that of the other diets. Moreover, the presence of RSP and CoQ10 may improve intestinal homeostasis by inhibiting the propagation of Vibrio. Compared to FM diet and RSP diet, supplementation of CoQ10 significantly improved the compressive capacity of L. vannamei against the acute low salinity challenge, as indicated by higher survival rates as well as higher activities of T-AOC and higher transcript levels of SOD, HSP70, and Relish gene. Our findings demonstrated that RSP could serve as a novel FM and CoQ10 could serve as a prospective feed additive to help L. vannamei to overcome environmental stresses.